The Influence of Social Interaction, Digital Celebrities Relationship, and Sale Proneness to Online Impulse Buying in Social Commerce - Ismeralda Putri Hasiani; Triana Rahajeng Hadiprawoto (Publikasi Indonesia, 2024)
This research examines factors influencing consumers' impulse buying behavior in social commerce. This study adopts a quantitative approach. The research was conducted in Indonesia. The research population is TikTok app users who frequently use the TikTok Shop feature. This study reports the responses of 303 respondents using non-probability and purposive sampling techniques. Data were primarily gathered through self-reported online questionnaires. Partial Least Square (PLS) was then used to test the hypothesized relationships. This study's results indicate that social interactions, parasocial relationships with digital celebrities, and sale proneness are proven to influence the urge to buy impulsively, resulting in impulse buying behavior. Our study highlights the importance of online social interaction, parasocial relationships with digital celebrities, and sale proneness in influencing the urge to buy impulsively, resulting in impulse buying behavior. To our knowledge, this study is the first to find what caused impulse buying in social commerce in Indonesia. Almost no previous research has examined sale proneness as a moderating role, especially in developing countries. Social commerce must focus on creating a conducive buying and selling environment in social commerce, creating healthy price competition with conventional business actors and MSMEs, limiting and preventing market monopoly, and limiting or even prohibiting the sale of cheap products originating from China.